Real-time Visualisasi Temperatur Pada NTC Sensor Array menggunakan Metode Interpolasi Gaussian berbasis Python - Joni Joni; Sabar Sabar; Kisna Pertiwi; M. Ikhsanudin; Leo Sinambela (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Thermal camera technology has been rapidly advancing in the process of remotely measuring temperature. In addition, thermal cameras can also be used to detect gas, water, and other fluid leaks by measuring the temperature changes in the measured object, such as water pipes within walls that cannot be seen directly with the naked eye. However, thermal cameras have limitations in directly measuring dynamic temperature, such as in electric motors mounted on engine blocks. Moreover, there is a need for acquiring data on temperature changes that can be stored and displayed in real-time. The aim of this research is to develop a basic prototype capable of measuring the temperature of the target object and displaying it directly, with the displayed data also being stored in a database. The hardware used for measurements in this study consists of an array of 36 NTC sensors, which are read by the ADC on each ESP-12K microcontroller. The measured data is sent from the microcontroller to the computer via serial communication in the form of voltage values, which are then converted into resistance and temperature values on the computer. For the temperature array visualization process, the author uses Python programming language and the Gaussian Interpolation method.